Optimal annual body mass index change for preventing spontaneous preterm birth in a subsequent pregnancy - Sho Tano; Tomomi Kotani; Takafumi Ushida; Masato Yoshihara; Kenji Imai; Tomoko Nakano-Kobayashi; Yoshinori Moriyama; Yukako Iitani; Fumie Kinoshita; Shigeru Yoshida; Mamoru Yamashita; Yasuyuki Kishigami; et al. (Scientific Reports, 2022)
Abstract Preterm birth (PTB) is a leading cause of neonatal morbidity and mortality. Although PTB is known to recur, interpregnancy preventive strategies for PTB have not been established to date. Annual BMI change can serve as a specific target value for preventing obstetric complications during interpregnancy care/counseling. This value can also account for age-related weight gain (0.2 kg/m2/year). In a multicenter retrospective study, we investigated the optimal annual BMI change for preventing PTB recurrence using the data of individuals who had two singleton births from 2009 to 2019. The association between annual BMI change and spontaneous PTB (sPTB) was analyzed by separating cases of medically indicated PTB (mPTB) from those of sPTB. Previous history of sPTB was strongly associated with sPTB in the subsequent pregnancy (adjusted odds ratio [aOR], 12.7; 95% confidence interval [CI], 6.5–24.8). Increase in annual BMI was negatively associated with sPTB (aOR, 0.6; 95% CI 0.5–0.9). The sPTB recurrence rate was significantly lower in patients with an annual BMI change of ≥ 0.25 kg/m2/year than in those with an annual BMI change of < 0.25 kg/m2/year (7.7% vs. 35.0%, p = 0.011). Our findings suggest that age-related annual BMI gain between pregnancies may help prevent sPTB recurrence.